Programa minha casa minha vida: Avaliaç\~oes de aderência ao déficit habitacional e de acesso a oportunidades urbanas - Cleandro Krause; Vanessa Gapriotti Nadalin; Rafael Henrique Moraes Pereira; Pedro Reis Sim\~oes (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– This article is a contribution of the Institute for Applied Economic Research (Instituto de Pesquisa Econômica Aplicada - Ipea) to the evaluation of the My House My Life Program (Minha Casa Minha Vida - PMCMV) carried out within the scope of the Public Policy Monitoring and Evaluation Council Conselho de Monitoramento e Avaliaç\~ao de Políticas Públicas (Conselho de Monitoramento e Avaliaç\~ao de Políticas Públicas - CMAP) of the Brazilian Federal Government. The relevance of PMCMV for recent housing provision in Brazil, as well as for the economic dynamism of the real estate sector, is undeniable. However, doubts remained about the focus of the program, in its range aimed at lower-income families, operated by the Residential Lease Fund (Fundo de Arrendamento Residencial - FAR). This question refers to the inclusion of borrowers who, in their previous housing situation, would (or would not) be part of the contingent of families in housing deficit. In addition, the provision of the program has been criticised due to the predominance of housing estates in peripheral locations, far from jobs and urban equipment. This evaluation sought to bring answers to both questions. In the twenty most populous municipalities in the country, the existence of a previous housing deficit of program borrowers was calculated, using data of the Registry of Social Programs (Cadastro Único de Programas Sociais - CadÚnico). In the same sample of municipalities, indicators of accessibility to jobs and basic health and education services, reachable from each of the PMCMV/FAR projects, were measured through the use of Ipea's Access to Opportunities project platform. The results allow measuring the adherence of the program to the housing deficit, finding that around 31% of borrowers would be in a situation of housing deficit in their previous home. The incidence of housing deficit was 43% higher among PMCMV/FAR borrowers than among families that did not benefit from the program. This finding may reveal that, in general, there was a good focus on the beneficiaries, although there is room for improvement. Regarding access to opportunities, the main results point out that, in almost all the cities that were analyzed, the values shown by the PMCMV/FAR projects were worse when compared to the average accessibility of people who live in slums or in low-income households (up to 1 minimum wage per capita). Although these differences are also present in access to schools and health services, the worst results are shown in the dimension of access to jobs. It is suggested that opportunities for improvement would be, either in greater integration between housing and transport policies, or in public policies that mitigate spatial segregation, through the use of better located land in these large cities, to the provision of housing developments of social interest. Such an option could include vacant land plots owned by the Federal Union.
Keywords: C13; D22; D24; E22; H12; H54; O16; 330; Programa Minha Casa Minha Vida; housing deficit; access to oportunities; urban mobility; urban insertion; Cadastro Único